2024
DOI: 10.2486/indhealth.2023-0144
|View full text |Cite
|
Sign up to set email alerts
|

Predicting physical and mental health status through interview-based evaluation of work stress: initial attempts to standardize the interviewing method

Keita KIUCHI,
Xin KANG,
Ryota NISHIMURA
et al.

Abstract: This study conducted an interview-based stress evaluation that considered the psychosocial models of work stress and verified the evaluation's predictive validity.A four-stage assessment comprising a pre-survey, pre-interview questionnaire, stress assessment interview, and post-survey after one month was conducted with 50 Japanese workers. Additionally, 16 occupational health professionals provided stress evaluations based on recorded interview videos. Variables based on intraclass correlation coefficients (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…In a previous study, an interview-based stress assessment significantly predicted self-reported mental symptoms, burnout, and well-being. 30 Taken together with the results of the present study, interview-based stress assessment can be broadly used as a predictor, but high stress causally leads only to reduce well-being. Thus, when implementing measures aimed at preventing or eliminating high stress, not only self-reported health status but also well-being as an outcome should be measured to appropriately capture the effects.…”
Section: Main Findingssupporting
confidence: 65%
See 4 more Smart Citations
“…In a previous study, an interview-based stress assessment significantly predicted self-reported mental symptoms, burnout, and well-being. 30 Taken together with the results of the present study, interview-based stress assessment can be broadly used as a predictor, but high stress causally leads only to reduce well-being. Thus, when implementing measures aimed at preventing or eliminating high stress, not only self-reported health status but also well-being as an outcome should be measured to appropriately capture the effects.…”
Section: Main Findingssupporting
confidence: 65%
“…This study investigated the causal effects of high stress, as assessed during interviews, on mental and physical health status 1 month later as a secondary analysis of a previously published study. 30 This study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines to ensure rigorous and transparent reporting of our findings. A detailed list of page numbers and corresponding text, which confirm its compliance with the STROBE statement, is provided in the Appendix (http://links.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations